Technical analysis and stock market profits - Schabacker, Richard W. (New Delhi, 2008)
This great work by Richard W. Schabacker is a worthy addition to each and every technical analyst's and trader's library. Schabacker's "pioneering research" represents one of the finest works ever produced on technical analysis, and this book remains an example of the highest order of analytical quality and incisive trading wisdom. Originally devised as a practical course for investors, it is as alive, vital and instructional today as the day it was written. Schabacker presents technical analysis as a totally organized subject and comprehensively lays out the various important patterns, formations, trends, support and resistance areas, and associated supporting technical detail. He presents factors that can be confidently relied on, and gives equal attention to the blemishes and weaknesses that can upset the best of analytical forecasts: factors which investors would do well to absorb and apply when undertaking the fascinating game of price, time and volume analysis.
Keywords: Stock Markets